Journal of hydrodynamics. Ser. B. - Zhongguo chuan bo ke xue yan jiu zhong xin (China Ocean Press, 1990)
The Journal of Hydrodynamics reflects the research activities in various areas of hydrodynamics related to ocean and ship engineering, environmental engineering, water conservancy and hydropower engineering, energy exploration, ocean and environmental engineering, and chemical engineering.
Keywords: Hydrodynamics : Periodicals; Hydrodynamique : Périodiques; Hydrodynamics; Engineering; hydrodynamica; hydrodynamics; hydraulica; hydraulics; waterbouwkunde; hydraulic engineering; Hydraulic Engineering; Waterbouwkunde